Calculation of resonant frequencies of a shorting pin‐loaded ETMA with ANN. Issue 3 (March 2014) - Can, Sultan; Kapusuz, Kamil Yavuz; Aydin, Elif
Abstract This article describes an artificial neural network (ANN) model to accurately estimate the lower and upper operating frequencies of a shorting pin‐loaded dual‐band equilateral triangular microstrip antenna. A multilayer feed forward network is used for training in this ANN‐based model. The results obtained from this study are compared with other theoretical and measured results from the available literature. The average percentage error for both upper and lower frequencies is 1%, which corresponds to a considerable improvement achieved over the recent study, having the most accurate results. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:660–663, 2014